Factors Related to the Midwaves’ Work Performance on Anemic Pregnant Women Manegement in Singkawang City, Kalimantan Barat - U. Evi Nasla; Laksmono Widagdo; Cahya Tri Purnami (Jurnal Manajemen Kesehatan Indonesia, 2013)
WHO memperkirakan sekitar 40% kematian ibu di negara berkembang berkaitan dengan anemia dalam kehamilan. Deteksi kasus anemia pada kehamilan belum dilakukan sesuai dengan standar pengelolaan anemia pada kehamilan. Maka dilakukan analisis faktor- faktor yang mempengaruhi kinerja bidan dalam pengelolaan anemia pada kehamilan di Kota Singkawang.Jenis penelitian survei analitik dengan pendekatan Retrospektif. Jumlah sampel 52 bidan Puskesmas wilayah Kota Singkawang dipilih secara proportional stratified random sampling dengan kriteria inklusi. Pengumpulan data dengan kuesioner terstruktur dan observasi langsung. Data dianalisis dengan uji korelasi Spearman Rank dan Regresi Logistik.Hasil penelitian mayoritas responden berusia antara 20-35 tahun (63,5%), pendidikan DIII/DIV/S1 Kebidanan (90,4%), masa kerja ≥10 tahun (55,8%). Kinerja bidan mempunyai kategori baik (59,6%), pengetahuan baik (51,9%), sarana prasarana lengkap (53,8%), kepemimpinan baik (63,5%), motivasi baik (55,8%), komunikasi baik (53,8%). Semua variabel bebas (pengetahuan, sarana prasarana, kepemimpinan, motivasi dan komunikasi) hubungan dengan kinerja bidan dalam pengelolaan anemia pada kehamilan (p < 0,05). Variabel yang berpengaruh terhadap kinerja bidan dalam pengelolaan anemia pada kehamilan adalah pengetahuan (p=0,002) dan kepemimpinan (p=0,006). Disarankan untuk Dinas Kesehatan dan Puskesmas memfasilitasi bidan dalam meningkatkan pengetahuan dan ketrampilan melalui pendidikan formal dan pelatihan-pelatihan, meningkatkan supervisi dan rapat koordinasi, menyediakan sarana prasarana pendukung dalam pengelolaan anemia. World Health Organization estimated that about 40% maternal mortality in developing countries was related to anemia during pregnancy. Detection of anemia cases during pregnancy was not conducted according to standard of management for anemia during pregnancy. Therefore, analysis factors affecting work performance of midwives in the management of anemia during pregnancy in Singkawang city. This was an analytical survey with retrospective approach. The number of samples was 52 midwives of primary healthcare centers in Singkawang city. They were selected using proportional stratified random sampling method, and they fulfilled inclusion criteria. Data were collected using structured questionnaire and direct observation. Spearman Rank correlation test and logistic regression were applied in the data analysis. Results of the study showed that majority of respondents’ age was 20-35 years old (63.5%), highest level of education was DIII/DIV/S1 midwifery (90.4%), work period was 10 years or more (55.8%). Work performance of midwives was in a good category (59.6%), respondents’ knowledge were good (51.9%), facilities were complete (53.8%), leadership was good (63.5%), motivation was good (55.8%), communication was good (53.8%). All independent variables (knowledge, facilities, leadership, motivation, and communication) were associated with work performance of midwives in the management of anemia during pregnancy (p< 0.05). Variables affecting the work performance of midwives in the management of anemia during pregnancy were knowledge (p= 0.002) and leadership (p= 0.006). Suggestions for district health office and primary healthcare centers were to facilitate midwives to improve their knowledge and skills through formal education and trainings, to improve supervision and coordination meetings, to provide supporting facilities in the management of anemia.